Innovation for Making Portable Induction Furniture as a Solution for System Waste Handling Post-vaccination COVID-19 Vaccine - Ridwan Abdurrahman; Ahmad Kafrawi Nasution; Ayub Satria (METAL: Jurnal Sistem Mekanik dan Termal, 2022)
The world was shocked by the outbreak of a new virus called Coronavirus Disease 2019 (COVID-19) in 2020. The use of personal protective equipment in the community during a pandemic resulted in an increase in the amount of medical waste. Syringe is one of the medical waste from the COVID-19 pandemic which is classified as metal waste. One of the solutions offered is a medical waste incinerator. By studying the medical waste incinerator model in hospitals, the researchers finally took the initiative to design a simple incinerator. The incinerator to be used is a portable induction type. It is hoped that the use of this incinerator will be able to overcome the existing medical waste problem. Keywords: Evaluation, Incinerator, Garbage, Induction.